IPNV with high and low virulence: host immune responses and viral mutations during infection - Skjesol, Astrid; SkjÆveland, ingrid; Elnæs, Marianne; Timmerhaus, Gerrit Frantz; Fredriksen, Børge Nilsen; Jørgensen, Sven Martin; Krasnov, Aleksei; Jørgensen, Jorunn B (Virology Journal, 2011)
Infectious pancreatic necrosis virus (IPNV) is an aquatic member of the Birnaviridae family that causes widespread disease in salmonids. IPNV is represented by multiple strains with markedly different virulence. Comparison of isolates reveals hyper variable regions (HVR), which are presumably associated with pathogenicity. However little is known about the rates and modes of sequence divergence and molecular mechanisms that determine virulence. Also how the host response may influence IPNV virulence is poorly described. In this study we compared two field isolates of IPNV (NFH-Ar and NFH-El). The sequence changes, replication and mortality were assessed following experimental challenge of Atlantic salmon. Gene expression analyses with qPCR and microarray were applied to examine the immune responses in head kidney. Significant differences in mortality were observed between the two isolates, and viral load in the pancreas at 13 days post infection (d p.i.) was more than 4 orders of magnitude greater for NFH-Ar in comparison with NFH-El. Sequence comparison of five viral genes from the IPNV isolates revealed different mutation rates and Ka/Ks ratios. A strong tendency towards non-synonymous mutations was found in the HRV of VP2 and in VP3. All mutations in VP5 produced precocious stop codons. Prior to the challenge, NFH-Ar and NFH-El possessed high and low virulence motifs in VP2, respectively. Nucleotide substitutions were noticed already during passage of viruses in CHSE-214 cells and their accumulation continued in the challenged fish. The sequence changes were notably directed towards low virulence. Co-ordinated activation of anti-viral genes with diverse functions (IFN-a1 and c, sensors - Rig-I, MDA-5, TLR8 and 9, signal transducers - Srk2, MyD88, effectors - Mx, galectin 9, galectin binding protein, antigen presentation - b2-microglobulin) was observed at 13 d p.i. (NFH-Ar) and 29 d p.i. (both isolates). Mortality and expression levels of the immune genes were directly related to the rate of viral ...